2016
DOI: 10.1039/c5cp05622e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular principle of the cyclin-dependent kinase selectivity of 4-(thiazol-5-yl)-2-(phenylamino) pyrimidine-5-carbonitrile derivatives revealed by molecular modeling studies

Abstract: Due to the high sequence identity of the binding pockets of cyclin-dependent kinases (CDKs), designing highly selective inhibitors towards a specific CDK member remains a big challenge. 4-(thiazol-5-yl)-2-(phenylamino) pyrimidine derivatives are effective inhibitors of CDKs, among which the most promising inhibitor 12u demonstrates high binding affinity to CDK9 and attenuated binding affinity to other homologous kinases, such as CDK2. In this study, in order to rationalize the principle of the binding preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…According to previous studies, US simulations can also accurately rank the binding affinities of different inhibitor–protein systems . As shown in Table , it can be observed that the PMF values of the four systems are −20.12, −15.10, −15.15, and −12.93 kcal mol −1 , respectively, which is in satisfactory agreement with the experimental date.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…According to previous studies, US simulations can also accurately rank the binding affinities of different inhibitor–protein systems . As shown in Table , it can be observed that the PMF values of the four systems are −20.12, −15.10, −15.15, and −12.93 kcal mol −1 , respectively, which is in satisfactory agreement with the experimental date.…”
Section: Resultssupporting
confidence: 79%
“…The calculated binding affinities are much stronger than the experimental data. According to the previous studies, MM/GBSA usually provides reliable ranking results rather than accurately predicting the absolute binding free energies . According to the calculation results, COM25 has the strongest inhibition to GSK3β than CDK2 and its predicted binding free energy for GSK3β is the highest.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MM/GBSA method is a practical approach in current computer-aided drug design field which can balance accuracy and speed. [62,[71][72][73][74][75] Although deviation is inevitable when MM/GBSA method is utilized for free energy calculation due to its approximation processing, this bias is eliminated when comparing free energy of different ligands to the same target. [76,77] This method is still very popular and is used by many researchers because of its good correlation with the experimental values.…”
Section: Binding Free Energy and Decomposition Analysismentioning
confidence: 99%